ECOSOC Dialogue: a federal structure for the UN Development System? - Max-Otto Baumann (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The 2030 Agenda, with its 17 Sustainable Development Goals, adds new urgency to the reform of the UN Development System (UNDS). If we wish the UNDS to play a decisive role in sustainable development, it must be made fit for purpose. UN member states have recognized the need for action. In December 2014, they launched a state dialogue in the Economic and Social Council (ECOSOC) in order to discuss the longer-term positioning of the UNDS and present concrete reform proposals by mid-2016. To date, no breakthrough has been achieved. Participating states are opting for incremental reforms within existing mandates and structures, which are unlikely to bring the necessary changes. The general restraint on tackling ambitious reforms stands in contrast to the current comparatively favourable context for repositioning the UNDS. The 2030 Agenda, adopted successfully last September at the greatest ever UN summit so far, requires a revamp of the UNDS so that it can effectively and efficiently assist member states in implementing both their own and collective development interests. The increased awareness of global problems associated with globalisation and climate change has led to calls to give the UNDS better global problem-solving capacities. Additionally, it is by no means only OECD states that are deploring the fragmentation and incoherence of the UNDS. The second phase of the ECOSOC Dialogue now provides an opportunity to take the necessary steps towards an ambitious UNDS reform. Emphasis should be placed on a more comprehensive reform package. The present paper proposes a federal structure for the UNDS, based on two elements: (1) a strengthening of the central, system-wide governance capacity, while (2) largely maintaining the subsidiary independence of the UN agencies. Significant elements of a federally structured UNDS are as follows: Reinforcement of the ECOSOC as a forum for the intergovernmental, system-wide governance of the UNDS, and creation of a corresponding administrative entity of equal weight (Development Commission); Expansion of existing system-wide funding mechanisms based on voluntary contributions, and the introduction of a new component of assessed contributions; Retention of the far-reaching subsidiary independence of the funds, programmes and specialised agencies, but on the basis of a review of their mandates; Reform of governance structures, including a geographically fair distribution of seats and the representation of various stakeholder groups. Although these reforms are ambitious, they may well meet with political acceptance from a large majority of states. It is now time to overcome the formation of rival North and South camps, and to focus on common interests via an open, inclusive and constructive dialogue.
Keywords: 330; Agenda 2030; Regionale + globale + transnationale Governance